The Effect of Papaya (Carica papaya) Juice on Body Weights of The Municipal Police Officers in Ternate (Polres Ternate) (International Journal of Scientific Research and Management (IJSRM), 2021)
Background: Overweight and obesity issue occur in Municipal Police Officers in Ternate (Polres Ternate). A pilot study has been done in Polres Ternate and found that there were 70 cases of overweight Police Officers. According to the attending health care profession, the treatment of those overweight cases had been done through exercise but without diet management. This is an experimental study with pre- and post-test in both control and intervention group. Population in this study was 70 Overweight Municipal Police Officers in Ternate (Polres Ternate). The sample size in this study was 30 respondents which were were randomly selected and divided into 15 in each of intervention and control group. Intervention group was given papaya juice while control group was given placebo for 60 days. The results show that there was significant different body weight between before and after intervention in intervention group but there was non-significant different body weight between before and after intervention in control group. There was non-significant different body weight between intervention group and control group after intervention. Body weight loss happened in intervention group which caused by papaya juice administration together with the education and motivation of the respondents. Nevertheless, there was no significant different between intervention group and control group after intervention.